Potensi Beban Pencemaran Limbah Sektor Pertanian, Perkebunan dan Peternakan Terhadap DAS Bengawan Solo di Kabupaten Boyolali - Ningsih, Sepfiana Dari; Khotimah, Kusnul; Risnanti, Fibula; Nugrahanti, Dinda Ayu; Ahmad, Radix Dzakiya; Maulana, Rashyid Muttaqim (LaGeografia, 2020)
The Central Java Province is one of Province with a major agricultural livelihood. Central Java is also rice, corn, and soybean, which in 2019 the productivity of rice was 57.53 million per hectare. The rice land in Central Java is approximately 1.68 million hectares and provides 9.65 million tons of rice Â (BPS , 2020). The agricultural sector also has a large multifunctional value in terms of improving food security, welfare of farmers, and also helps preserve the environment (Tannaim, Hasriyanti, & Nasiah, 2019). The goal for the study is to find out the potential burden of waste on agricultural, plantation, and livestock at Bengawan Solo Watershed in Boyolali Regency. This research using a quantitative descriptive method. Based on analysis of the livestock sector is by far the largest concentrations than other sectors, which could be proved that the highest wast-producing category of Cepogo dentures with a 2027 tons per year of body waste and a cost-burden of 26196 tons per year. This means that the livestock sector growing in Boyolali Regency could potentially produce a burden of pollution that could disrupt water quality in a Bengawan Solo Watershed.